Long‐term variability of surface nutrient concentrations in the North Pacific. Issue 7 (5th April 2016) - Yasunaka, S.; Ono, T.; Nojiri, Y.; Whitney, F. A.; Wada, C.; Murata, A.; Nakaoka, S.; Hosoda, S.
Abstract: We present the spatial distributions and temporal changes of the long‐term variability of surface nutrient concentrations in the North Pacific by using nutrient samples collected by volunteer ships and research vessels from 1961 to 2012. Nutrient samples are optimally interpolated onto 1° × 1° monthly grid boxes. When the Pacific Decadal Oscillation is in its positive phase, nutrient concentrations in the western North Pacific are significantly higher than the climatological means, and those in the eastern North Pacific are significantly lower. When the North Pacific Gyre Oscillation is in its positive phase, nutrient concentrations in the subarctic are significantly higher than the climatological means. The trends of phosphate and silicate averaged over the North Pacific are −0.012 ± 0.005 µmol l −1  decade −1 and −0.38 ± 0.13 µmol l −1  decade −1, whereas the nitrate trend is not significant (0.01 ± 0.13 µmol l −1  decade −1 ). Key Points: Surface nutrient concentrations in the North Pacific are optimally interpolated The PDO‐ and NPGO‐ related nutrient variability are presented Phosphate and silicate trends are negative, but nitrate shows no trend